2021
DOI: 10.1186/s13578-021-00605-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurohormonal activation induces intracellular iron deficiency and mitochondrial dysfunction in cardiac cells

Abstract: Background Iron deficiency (ID) is common in patients with heart failure (HF) and is associated with poor outcomes, yet its role in the pathophysiology of HF is not well-defined. We sought to determine the consequences of HF neurohormonal activation in iron homeostasis and mitochondrial function in cardiac cells. Methods HF was induced in C57BL/6 mice by using isoproterenol osmotic pumps and embryonic rat heart-derived H9c2 cells were subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
(71 reference statements)
1
20
0
Order By: Relevance
“…Moreover, Haddad et al highlighted the importance of iron-regulatory proteins (IRP-1 and IRP-2) to the heart in securing myocardial iron [ 178 ]. More recently, Tajes et al demonstrated in mice with isoproterenol (β-adrenoceptor agonist)-induced HF that neurohormonal activation leads to MID accompanied by mitochondrial dysfunction by reducing extracellular iron uptake and increasing intracellular iron release [ 33 ]. These findings were validated using embryonic rat heart-derived H9c2 cells challenged with norepinephrine and/or angiotensin 2, which led to similar results [ 33 ].…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Haddad et al highlighted the importance of iron-regulatory proteins (IRP-1 and IRP-2) to the heart in securing myocardial iron [ 178 ]. More recently, Tajes et al demonstrated in mice with isoproterenol (β-adrenoceptor agonist)-induced HF that neurohormonal activation leads to MID accompanied by mitochondrial dysfunction by reducing extracellular iron uptake and increasing intracellular iron release [ 33 ]. These findings were validated using embryonic rat heart-derived H9c2 cells challenged with norepinephrine and/or angiotensin 2, which led to similar results [ 33 ].…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
“…More recently, Tajes et al demonstrated in mice with isoproterenol (β-adrenoceptor agonist)-induced HF that neurohormonal activation leads to MID accompanied by mitochondrial dysfunction by reducing extracellular iron uptake and increasing intracellular iron release [ 33 ]. These findings were validated using embryonic rat heart-derived H9c2 cells challenged with norepinephrine and/or angiotensin 2, which led to similar results [ 33 ]. This implies that neurohormonal activation worsens HF by decreasing myocardial iron, suggesting that ID may be more than merely a comorbidity.…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that patients with ID presented higher noradrenaline levels and that this increased neurohormonal activation was related with impaired iron homeostasis [ 15 ]. Moreover, we have recently demonstrated that key iron regulating elements were altered in mice with HF, leading to myocardial ID, and we have shown that the stimulation of cardiac cells with norepinephrine and angiotensin, altered critical iron regulation components, generating intracellular ID and mitochondrial dysfunction [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iron regulation is impaired in the cardiomyocytes of patients with HF [ 17 ] and cardiomyocyte contractility is reduced in the presence of myocardial ID [ 18 ]. Moreover, recent experimental data suggest that HF neurohormonal activation induces myocardial iron depletion leading to impaired mitochondrial inducing structural and functional modifications in biological pathways in cardiomyocyte iron regulating elements that could provoke an increase in iron release and a reduction in iron uptake [ 19 ].…”
Section: Introductionmentioning
confidence: 99%